2018
DOI: 10.2147/copd.s172639
|View full text |Cite
|
Sign up to set email alerts
|

Significances of spirometry and impulse oscillometry for detecting small airway disorders assessed with endobronchial optical coherence tomography in COPD

Abstract: BackgroundSpirometry confers limited value for identifying small-airway disorders (SADs) in early-stage COPD, which can be detected with impulse oscillometry (IOS) and endobronchial optical coherence tomography (EB-OCT). Whether IOS is useful for reflecting small-airway morphological abnormalities in COPD remains unclear.ObjectivesTo compare the diagnostic value of spirometry and IOS for identifying SADs in heavy-smokers and COPD based on the objective assessment with EB-OCT.MethodsWe recruited 59 COPD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
2
36
1
1
Order By: Relevance
“…Small airway disease was detected with IOS even in early stages and linked to typical symptoms such as dyspnoea 45 . In early stages, IOS parameters outperformed conventional spirometry when differentiating heavy smokers with normal lung function as well as early-stage COPD 46 20 . Even in absence of spirometric obstruction, LCI was already pathologically altered 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Small airway disease was detected with IOS even in early stages and linked to typical symptoms such as dyspnoea 45 . In early stages, IOS parameters outperformed conventional spirometry when differentiating heavy smokers with normal lung function as well as early-stage COPD 46 20 . Even in absence of spirometric obstruction, LCI was already pathologically altered 22 .…”
Section: Discussionmentioning
confidence: 98%
“…42 Recent studies have shown associations between resistance variations and the degree of morphologic abnormalities of small airways assessed with endobronchial optical coherence tomography in COPD and heavy smokers. 43 It should be noted that these parameters are also influenced by the shunt impedance from the upper airway, as well as by the tissue resistance. The changes observed indicate increasing heterogeneity of the respiratory system with the progression of the disease.…”
Section: Dovepressmentioning
confidence: 99%
“…Compared with spirometry, it is independent of the subjects’ efforts because of the externally superimposed oscillation signals [ 8 ]. Furthermore, it may have higher sensitivity in detecting SAD and seems to be better correlated with small airway structures [ 9 11 ]. Since IOS could reflect the viscous property of the respiratory system by resistance (Rrs), elastic and inertial property by reactance (Xrs), it might provide deeper information on individuals’ pathology changes when applied coupled with spirometry.…”
Section: Introductionmentioning
confidence: 99%